Job burnout among the teaching librarians at a selected academic library in Malaysia / Noor Hasanah Mohd Hanafi, Saidatul Akmar Ismail and Nur Adlina Zulkifli - Mohd Hanafi, Noor Hasanah; Ismail, Saidatul Akmar; Zulkifli, Nur Adlina (Universiti Teknologi MARA, 2020)
This study aims to determine if there are any feelings of burnout among the Teaching librarians at the IL department located in an academic library of a research University in Malaysia. This research is held at the IL department at a selected academic library of a research University in Malaysia. MBI (Maslach and Jackson, 1986) is used to measure job burnout. The MBI contains three subscales: emotional exhaustion, depersonalization, and personal accomplishment. The nine items in the emotional exhaustion subscale describe feelings of being emotionally overextended and exhausted by one's work. The five items in the depersonalization subscale describe an unfeeling and impersonal response towards one's care or service recipients. The subscale of personal accomplishment lists eight items to describe feelings of competence and achievement in one's work with people